Power electronics and converter technology - Kholod, O. I.; Krylov, D. S. (National technical university "Kharkiv polytechnic institute", 2022)
It is recommended to use those teaching aid when performing laboratory work on the discipline "Power electronics and converter technology" when studying the work of: smoothing filters in various schemes of uncontrolled rectifiers; controlled rectifiers with different types of load; pulse-width converters; autonomous current and voltage inverters on a virtual laboratory bench (VLB), which is a personal computer (PC) with the MatLab / Simulink software package installed on it. The purpose of virtual laboratory works is to consolidate theoretical knowledge, through calculations, modeling and detailed study of electrical processes in various schemes of semiconductor converters in steady-state and transient operating modes. The virtual laboratory bench allows you to study the parameters of circuits and their operation modes within a wide range.
Keywords: teaching aid; smoothing filters; controlled rectifier; model building steps; pulse width converters; calculation of the scheme; autonomous voltage inverter; capacitive filter